Features of the application of the decisions of the European court of human rights by Ukrainian courts in tax cases - Igor Babin (DANUBE: Law, Economics and Social Issues Review, 2020)
The purpose of this article is to explore the subject of applying to the European Court of Human Rights in tax cases, the place of decisions of the European Court of Human Rights in the system of sources of tax law, the problems arising from the application of ECtHR decisions by Ukrainian courts in tax cases. The research was carried out using formal-dogmatic, system-structural, comparative-legal, historical and other methods of scientific cognition. The author concludes that it is important to use the decisions of the European Court of Human Rights to resolve public law disputes, the subject of which is public finances. After all, the Ukrainian tax system and tax legislation, the tax status of taxpayers and tax authorities should be based on the fundamental principles enshrined in the Convention and which have repeatedly been systematically interpreted in the decisions of the European Court of Human Rights.
Keywords: 330; European Court of Human Rights; Tax Law; Case Law; Ukraine